The Association of Human Cytomegalovirus Infection of Male Genital Tract and Male Infertility (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: The human cytomegalovirus (HCMV) is a widely distributed virus among humans and is included within the sexually transmitted viruses. Because of its low detection rate in semen, the impact of HCMV on sperm formation and its vertical transmission within the sperm cells have not been studied sufficiently.                                                                                                     Objectives: To investigate the association of viral infections present in the lower genital tract of males and relationship among males infertility.Methods: ELISA and RT-PCR technique of 100 semen and serum specimens, collected over 8 months from males investigated for infertility, were retrospectively assessed, by screening anti-human Herpes Simplex Virus (HCMV) IgM and IgG in the serum and detection of HSV DNA in seminal fluid.                                                                                        Results: One hundred seminal fluid and blood samples were taken from men and investigated for infertility over a period of 8 months from July 2016 to February 2017. The seminal fluids and serum of patients mentioned to the laboratory from the fertility clinics of Kamal AL-samarai hospital and outer clinics. The investigations were conducted to find the HCMV detection rate in the seminal fluid of infertile men and to evaluate the impact of the viral infection on the major sperm parameters. Blood and seminal fluid were collected from 100 infertile males. The results were shown that 24/100 (24.0%) were positive for IgM and 86/100 (86.0%) were positive for IgG of HCMV. In case of the control group, results were (1.0%) positive for anti-HCMV IgM antibodies, while (20.0%) positive for anti-HCMV IgG antibodies in a control group, using ELISA test.                           The PCR showed that out of 100 samples 24 (24.0%) gave positive results for HCMV patients, while 7 (7.0%) positive for HCMV in the control group.Conclusions: Using sensitive procedures for assays, seminal samples of asymptomatic infertile patients showed an unexpectedly high incidence of the sexually transmitted pathogens.